Perinatal mental health around the world: priorities for research and service development in France - Sutter-Dallay, Anne-Laure (BJPsych Int, 2020)
France has a long tradition of concern for maternal and perinatal mental health. However, the national organisation of psychiatric care does not yet provide structured guidelines on the organisation of perinatal psychiatric care. This paper provides an update on existing resources and their linkage to primary care and obstetric and paediatric services, as well as a review of current and future national priorities that are under development.